ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS DAN IMPLIKASINYA PADA CORPORATE VALUE - Aria Aji Priyanto (KRISNA: Kumpulan Riset Akuntansi, 2021)
This research objective to explore the factors that impact the firm's profitability viz. firm size, liquidity, and leverage and so determine its implications for Corporate Value. Corporate value is measured calculating with the Tobins Q Index. This type of research is comparative causal with a quantitative approach. The population of this research is the sub sector of Transportation company listed on the Indonesia Stock Exchange during 2010-2017 with the final sample determination of 7 companies. Data analysis method is using path analysis and the sobel test technique. Factors that affect profitability viz. firm size, liquidity, and leverage are only evidenced through liquidity which has a negative effect on profitability while profitability has a positive effect on corporate value. Firm size and leverage have no significant effect on profitability. Finally, Firm Size, Liquidity, and Leverage in this research weren't able to evaluate Corporate Value through profitability which functioned as an intervening variable